2008
DOI: 10.1002/jnr.21958
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral challenge with double‐stranded RNA elicits global up‐regulation of cytokine gene expression in the brain

Abstract: It is well established that mediators of peripheral inflammation are relayed to the brain and elicit sickness behavior via neuroinflammatory agents that target neuronal substrates. In the present study, we used double-stranded RNA (dsRNA), a viral replication intermediate, to mimic the acute phase of viral infection. C57BL/6 mice were injected intraperitoneally with 12 mg/kg of synthetic dsRNA, i.e., polyinosinic-polycytidylic acid (PIC). The treatment induced severe sickness behavior in the animals as reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 27 publications
(35 reference statements)
5
31
0
Order By: Relevance
“…At intraperitoneal doses comparable with those used here, increased concentrations of a wide range of inflammation-related chemokine genes has been reported as well as the classical cytokines 50,51 . Similar doses can also promote the CNS expression of interferons-a and b and interleukins IL-1b and IL-6 52,53 as well as TNFa 54,55 .…”
Section: Discussionmentioning
confidence: 77%
“…At intraperitoneal doses comparable with those used here, increased concentrations of a wide range of inflammation-related chemokine genes has been reported as well as the classical cytokines 50,51 . Similar doses can also promote the CNS expression of interferons-a and b and interleukins IL-1b and IL-6 52,53 as well as TNFa 54,55 .…”
Section: Discussionmentioning
confidence: 77%
“…It has been demonstrated that systemic administration of polyI:C induces mechanical pain hypersensitivity by activating microglia in the spinal cord in rats [31,49]. It also induces neuroinflammation in the brain, which is characterized by the expression of proinflammatory cytokines such as IL-1β, IL-6 and TNF-α [25,50]. These brain-derived cytokines also decrease nociceptive thresholds [51][52][53][54][55] and induce depressive-like behavior [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Poly I:C administration to mice induces a transient slight increase in core body temperature but a strong sickness behavioral response, assessed as a decrease in LMA and burrowing activity . This sickness response is accompanied by a marked increase in circulating IFN, IL-6 and TNF followed by CNS mRNA expression of the same cytokines and, to a lesser extent, IL-1 albeit IFN is not increased Gandhi et al, 2007;Konat et al, 2009). This cytokine profile is similar to that shown in Fig.2.…”
Section: Tlr3 Tlr7 Tlr8 and Tlr9: Nucleic Acidsmentioning
confidence: 97%